PP27 Terms used to describe key symptoms in out-of-hospital cardiac arrest by people calling 999 emergency medical services: a qualitative analysis of call recordings to two uk ambulance services. Issue 10 (28th September 2017) - Gibson, Josephine ME; Jones, Stephanie P; Hurley, Margaret; Auton, Mal; Leathley, Michael J; Sutton, Christopher J; Bangee, Munirah; Benedetto, Valerio; Chesworth, Brigit; Miller, Colette; O'Shea, Dawn; Quinn, Tom; et al.
Abstract : Background: Cardiac arrest outside hospital is a catastrophic medical emergency experienced by an estimated 60 000 people a year in the UK. The speed and accuracy with which cardiac arrest outside hospital is recognised by 999 call handlers is fundamental to improving the chance of survival, but is extremely challenging. We aimed to identify how cardiac arrest is actually described by callers during dialogues with 999 call handlers. Methods: Data was obtained from two acute NHS trusts and their two local ambulance trusts for all cases of suspected or actual out-of-hospital cardiac arrest (OHCA) or imminent medically witnessed cardiac arrest (MWCA) which led to transfer to one of the study hospitals, for a one year period (1/7/2013–30/6/2014). The 999 call recordings were listened to in full; words or phrases used by callers to describe clinical signs and symptoms were identified and clustered into key indicator symptoms using a thematic approach. Findings: 429 cases of cardiac arrest were identified, of which 246 (57.3%) were dispatched using a 'cardiac arrest' code. 6 callers (1.4%) used the term 'cardiac arrest' or a synonym. Key indicator symptoms reported most frequently were unconsciousness (64.8%), ineffective breathing (61.9%), and absent breathing (48.8%). Descriptors of conscious level included diverse colloquialisms and terms relating to reduced or fluctuating level of consciousness (17.2%). Descriptors of ineffective breathing included diverse terms relating to slow, fast, irregular, agonal, dyspnoea, and shallow breathing, plus nonspecific terms (e.g. 'breathing's funny); and 'don't know' statements. Conclusion: Callers' descriptors of key symptoms of OHCA are varied and include many colloquialisms. Call handler training should include awareness of likely descriptions, particularly of ineffective breathing, which may be more commonly reported than absent breathing.